Participation of adolescents in protection: dividends for all - Skeels, A; Sandvik-Nylund, M (Refugee Studies Centre, University of Oxford, 2012)
In order to keep children and adolescents safe, and improve their chances of living fulfilling lives, we need to listen and respond to their views and opinions on matters that affect them.